2019
DOI: 10.7150/jca.29874
|View full text |Cite
|
Sign up to set email alerts
|

Surgery plus chemotherapy improves survival of patients with extremity soft tissue leiomyosarcoma and metastasis at presentation

Abstract: Purpose : Extremity soft tissue leiomyosarcoma (LMS) with metastasis is a rare disease with a poor prognosis. The purpose of our study was to define clinical features of extremity soft tissue LMS with metastasis as well as to identify multivariable predictors of survival. Methods : During 1973-2015, 239 patients with metastatic extremity soft tissue LMS were identified from the Surveillance, Epidemiology, and End Results (SEER) program database. The prognostic analysis was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
2
10
0
3
Order By: Relevance
“…These results seem to align with the current literature detailing the aggressive nature of leiomyosarcoma, namely SLMS 5,15,16,18,19 . However, very few data describe the tumor characteristics of PLB, nor do they identify very many prognostic factors as these studies are mostly limited to case reports and small series 4,5,14,17,20–25 . Among the available literature for PLB, high histologic grade and tumor stage have demonstrated an association with distant metastases and local recurrence following surgical resection 22,26 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results seem to align with the current literature detailing the aggressive nature of leiomyosarcoma, namely SLMS 5,15,16,18,19 . However, very few data describe the tumor characteristics of PLB, nor do they identify very many prognostic factors as these studies are mostly limited to case reports and small series 4,5,14,17,20–25 . Among the available literature for PLB, high histologic grade and tumor stage have demonstrated an association with distant metastases and local recurrence following surgical resection 22,26 .…”
Section: Discussionsupporting
confidence: 81%
“…Mestiri et al published the results of 29 consecutive cases of histologically proven SLMS, and in addition to high rates of local recurrence (55%) and initial metastases, they note the majority of patients (69%) underwent surgery, and they suggest surgery appears to be the cornerstone of treatment for SLMS 13 . More recently, Qian et al 4 found surgery and chemotherapy together improved survival in patients with SLMS and metastases at presentation. Last, in their study of 7154 leiomyosarcoma patients, Gootee et al 16 demonstrated a lower risk of mortality in patients treated surgically with adjuvant radiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of metastatic LMS involves a multi-strategy in stepwise management, such as surgery, systemic treatment and radiotherapy [4]. Qian et al [21] analyzed data of 239 patients with metastatic extremity LMS, and found that surgery plus chemotherapy improved survival of these patients. However, in this case, radiotherapy and chemotherapy all failed.…”
Section: Discussionmentioning
confidence: 99%
“…We completed all statistical analyses by IBM SPSS Statistics 22. We defined cancer-specific survival (CSS) as the interval from diagnosis till death due to EC ( 10 , 11 ). We used the univariable Cox regression model to screen for statistically significant indicators associated with OS and CSS.…”
Section: Methodsmentioning
confidence: 99%